Computerspielforschung: Interdisziplinäre Einblicke in das digitale Spiel und seine kulturelle Bedeutung - Biermann, Ralf; Fromme, Johannes; Kiefer, Florian (Verlag Barbara Budrich, 2023)
Computer games are a significant constituent of today's digital media culture. Since the turn of the millennium scientific interest in digital games and their everyday importance has grown increasingly. Digital Game Studies are an interdisciplinary field of study, and the present book presents a broad insight into prevailing approaches, models, methods and results of different disciplines involved.